A mixed-methods study protocol on the psychosocial health of stroke survivors and their informal carers (CARESS): experiences, needs and quality of life - Ana Moura; Filipa Teixeira; Conceição Nogueira; Ana Henriques; Cláudia de Freitas; Elisabete Alves (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
Introduction: Surviving a stroke and caring for a survivor, impacts individuals' psychological health and quality of life, which may impose substantial costs on healthcare and social systems. This study aims to understand and explore the psychological health, experiences, needs and quality of life of Portuguese stroke survivors and their informal carers. Methods and analysis: This is a mixed-methods, observational study. The methodological strategy relies on 1) scoping review; 2) questionnaires to stroke survivors hospitalized between September 2018 and August 2019 in one of the 12 Stroke Units of the Northern Region Health Administration of Portugal and their informal carers, 18-24 months after the event (1775 survivors and 443 carers); and 3) semi-structured interviews to a subsample of stroke survivors (n = 49) and informal carers (n = 37); and 4) think tanks with stakeholders involved in the stroke rehabilitation process, namely stroke survivors, informal carers, researchers, and health and social professionals (n = 45). Descriptive and inferential statistics will be used to analyze the quantitative data, and content and interpretational analysis will be implemented to assess qualitative data. Ethics and dissemination: The study protocol was approved by the Ethics Committees of all the hospitals involved. The expected dissemination actions are effective tools in designing strategies that aim to promote knowledge on a needs-driven, socioethical sensitive basis, which will contribute to the implementation of a model of coproduction of health in the context of post-stroke care.